DEPICTION OF NATURALISM IN THE NOVEL TAFṢĪL THĀNAWĪ BY ADANIA SHIBLI - Misbahus Surur; Aulia Putri Oktaviani (Arabic Literature Department, 2025)
Unlike realist novels, whose characters can resist certain authorities, characters in naturalist novels cannot do so freely. Instead, they are often portrayed as swept up in pessimism and powerlessness. This study aims to explore the aspects of naturalism in the novel Tafṣīl Thānawī (Minor Detail), which depicts the condition of Palestine under Israeli occupation following the Nakba tragedy, using Zola’s naturalism as its theoretical lens. The research employs a descriptive–qualitative design: the novel is the primary source; secondary sources are books and journal articles on Shibli and Zola. Data were collected through close reading and note-taking, and analyzed via data reduction, data display, and conclusion drawing. The findings indicate five aspects of naturalism in Tafṣīl Thānawī, including determinism: impaired rational judgment, and a persistent focus on minute details. Settings: the Negev Desert, the hut of the Israeli military commander, and Ramallah. Pessimism: the Bedouin girl’s inability to resist and anxiety about traveling beyond her territory. Objectivity: third-person narration, the commander’s directives to soldiers, and the stark depiction of the girl’s burial. Plot twists: the Bedouin girl’s murder and the female journalist’s successful entry into Israeli territory.